THE USE OF POP UP BOOK MEDIA TO IMPROVE READING AT THE SEVENTH GRADE STUDENTS OF SMP N 3 ALAS BARAT - Darul Aqsha; Asbah Asbah; Humairah Humairah (Pendekar: Jurnal Pendidikan Berkarakter, 2018)
Abstract: Pop Up Book is the role of media is very important in the learning process. The presence of the Pop Up book media can support the learning process, facilitate students in understanding the learning material. This research was aimed to improve reading through Pop Up Book media the seventh grade students of SMP N 3 Alas Barat. The research belongs to collaborative action research which created a collaboration between the teacher of the seventh grade. The subject of this research was the seventh grade student of SMP N 3 Alas Barat which consists of 14 male students and 10 female students. The technique of collecting data was test, observation, and documentation. The technique of data analysis was descriptive, both quantitative and qualitative. The result of this research shows that there is an improvement of reading of the students of seventh grade in SMP N 3Alas Barat after using Pop Up Book as the media i.e. the average score from the average score at 65 before treatment (Pre-Action), it became 72 after the first cycle and reached 83 at the second cycle. The number of percentage was also increased from 36% before treatment (Pre-Action) became 64% at the first cycle and 96% at the second cycle. Besides, based on the observation, the students and their teacher also had an improvement in each cycle. The students are more active in learning process for each cycle.